Convict cichlid parents that stay with the same mate develop unique and consistent divisions of roles - Snekser,Jennifer L.; Itzkowitz,Murray (PeerJ, 2020)
Previous studies, largely on avian species, have suggested that pairs that are permanently monogamous and have biparental care develop a coordination over time that enhances offspring survival. If this is the case, we predicted that a parent involved in biparental care would develop a pattern of biparental care specific to a particular mate and remain consistent in that pattern over time but would lose this pattern if it were to change mates. We tested this prediction with the convict cichlid fish (Amatitlania nigrofasciata) which has biparental care that is both complex and flexible. In this species, each parent can perform all parental roles but typically shows a division of labor in which males typically defend against offspring predators while the female typically provides direct care to the offspring. At various times, the parents briefly switch roles. Our experiments revealed that pairs that remained together for two consecutive broods were more consistent in their parental behaviors, including time they spent near the intruder and in the nest compared to pairs that were comprised of individuals that had previously mated with other partners. Also individuals that remained with the same partner were also more consistent as a parental unit, maintaining their sex-specific roles of males defending aggressively against an intruder and females spending more time directly caring for young. While our experiment clearly support our prediction that individuals do develop unique coordination with specific individuals, convict cichlids in nature appear to be largely serially monogamous in which they mate only once before changing partners. Thus, it is likely this coordination may be available in many species that have biparental care but become adaptive when repeated matings become common.
Keywords: Behavior; Cichlid; Mate fidelity; Repeatability; Parental care; Division of roles